Índice de desenvolvimento humano municipal e seus indicadores: o desenvolvimento da região do alto curso da bacia hidrográfica do rio Apodi-Mossoró/RN - Castro, Antônio Carlos Gardel de Freitas (Universidade Federal Rural do Semi-Árido, 2017)
The main objective of this study was to investigate the evolution and behavior of the Municipal Human Development Index (IDHM) of the municipalities that compose the High Course Region of the Apodi/Mossoró River basin in the period 1991 to 2010. In this sense, The fundamental methodology adopted was the Geographic Information System - GIS. The indicators presented during the period allowed to verify that the greatest obstacle to the development of this region is directly related to the educational and income aspects of its inhabitants. Specifically, the IDHM education portrays that only four of the ten counties analyzed are in the low development category. While the others are presented with very low development. This situation is quite similar when analyzing the IDHM income. Specifically in 2010, all municipalities in this region were in a situation of low income development.
Keywords: IDHM; Educação; Saúde; Renda; education; health; income; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA